Morphological and biochemical responses of five tobacco cultivars to simultaneous infection with Pythium aphanidermatum and Meloidogyne incognita - KHAN, Mujeebur; HAQUE, Ziaul (Phytopathologia Mediterranea, 2013)
Five tobacco cultivars responded to Meloidogyne incognita inoculation with a 1.0–3.0 gall index. Inoculation with Pythium aphanidermatum resulted in a 0.33–2.66 root rot index, except cultivar RK-12 P3, which was without symptoms. The root rot symptoms became more severe in the plants concomitantly inoculated with fungus and nematode.The root rot symptoms also developed on cultivar RK-12 P3 in the presence of root-knot nematode. Soil populations of P. aphanidermatum were significantly greater in the presence than absence of M. incognita. Root- knot nematode population, however, showed a reverse trend, being less in the presence of root rot fungus. The fungus and nematode individually reduced the leaf pigments and plant growth of all cultivars except RK-12 P3 (P≤0.05), being greater in concomitantly inoculated compared with single pathogen inoculated plants. Phenol and salicylic acid contents of tobacco leaves gradually increased up to 15–20 days after planting, and thereafter, decreased. The greatest phenol and salicylic acid concentrations were recorded in tobacco plants concomitantly inoculated with the fungus and nematode.